DESAIN MAGANG, AKUISISI SKLILL SET, DAN BUDAYA KERJA INDUSTRI PADA PROGRAM UPSKILLING GURU KEJURUAN BIDANG SENI DAN EKONOMI KREATIF - Yuana, Cahya (Jurnal Pendidikan Seni dan Industri Kreatif, 2025)
Improving the Competency of Vocational Teachers in Vocational High Schools has a big goal. Vocational High Schools have the aim of preparing competent workers according to their concentration of expertise. The competence of Vocational High School graduates is therefore measured by the competence required by the world of work. Achieving vocational teacher competency in accordance with the needs of the world of work is a fundamental thing that must be fulfilled. One of the strategies for achieving vocational teacher competency to suit the world of work can be done through internships in the world of work. The arts and creative economy vocational teacher internship carried out by BBPPMPV Arts and Culture also aims to increase the competency of arts and creative economy vocational teachers. The question is what is the concept and form of arts and creative economy vocational teacher internships. The redefinition of industry as a place for vocational arts and creative economy teacher internships is an interesting thing to study, considering that arts and creative economy products are sometimes not everyday products. Arts production and the creative economy often depend on one particular momentum. In this regard, this research was conducted to photograph the concept of vocational teacher internships carried out by BBPPMPV Arts and Culture